Macrocellular Propagation Prediction for Wireless Communications in Urban Environments - Ekpenyong, Moses E. (2010)
In this paper, the signal propagation characteristics of urban environments are predicted by modeling important propagation parameters of the Code Division Multiple Access (CDMA) network for macrocells. The MOPEM propagation model has been selected as a model of choice due to its robustness in handling urban parameters. The model is simulated with some modifications using empirical data from the Visafone CDMA gathered from the Nigerian Telecommunications Limited (NITEL), Uyo, Nigeria and data from the field. From the simulation, we observe that propagation model parameters such as orientation angel, street width, building height, among others, has great influence on the system performance of CDMA wireless networks. We hope that with this research, systems designers could approach the installation of radio frequency equipment with some degree of confidence that the transmission link will effectively work, especially in urban areas.